(untitled) (Geneva, 1992)
Chap 1. Introduction, Chap 2. Strengthening technological capabilities,..., Chap 10. Inter - agency collaboration.
Keywords: Đổi mới công nghệ,Người lao động,Technological innovations,Employees,Employees,Employees,Employees; Ảnh hưởng của đổi mới công nghệ,Effect of technological innovations on,Effect of technological innovations on,Effect of technological innovations on,Effect of technological innovations on